Optimalisasi Pendidikan Anak Dengan Ngaji Adventure: Belajar, Bermain, dan Berkarya - Mu’tafi, Ali; Syahrul Huda, Muhammad Reza; Soraya, Rani; Khabiburrochman, Adam; Agustina, Neli; Prihatin, Siti; Arifa, Ziida; Setiyo, Ulfan; Mahfiroh, Nailil; Mutmainah, Arifatul; Febriyanti, Febriyanti; Lestari, Simping Puji; Suroyo, Sigit Adhi; Anggun, Anggun; Triawan, Adis (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The$ role$ of re$ligious e$ducation is vital in de$ve$loping the$ characte$r of childre$n from a young age$. Howe$ve$r, conve$ntional te$aching te$chnique$s fre$que$ntly do not e$ffe$ctive$ly e$ngage$ young le$arne$rs in the$ proce$ss of re$ading the$ Qur’an at Taman Pe$ndidikan Al-Qur’an (TPQ). Objective: This initiative$ se$e$ks to boost childre$n's inte$re$st and proficie$ncy in Qur’anic re$ading at TPQ Al-Huda by introducing a nove$l me$thod dubbe$d Ngaji Adve$nture$: Le$arning, Playing, and Cre$ating. Method: The$ approach applie$d in this initiative$ involve$s inte$ractive$ e$ducation through multime$dia re$source$s, fun game$s like$ outdoor activitie$s, and cre$ative$ assignme$nts utilizing re$cycle$d mate$rials. The$ program was carrie$d out in pe$rson ove$r se$ve$ral we$e$ks, involving 80 stude$nts from TPQ in various stimulating activitie$s. Result: The$ findings indicate$d a he$ighte$ne$d e$nthusiasm in childre$n towards le$arning to re$ad the$ Qur’an, along with e$nhance$me$nts in the$ir social inte$raction and cre$ativity. The$ childre$n e$xhibite$d gre$ate$r motivation to e$ngage$ in Qur’anic e$ducational activitie$s, compre$he$nd Islamic principle$s, and cultivate$ te$amwork abilitie$s through playful le$arning e$xpe$rie$nce$s Conclusion: The$ Ngaji Adve$nture$ initiative$ e$ffe$ctive$ly incre$ase$d childre$n's e$ngage$me$nt in Qur’anic e$ducation via a more$ e$njoyable$ and impactful te$aching style$.